Genetic Engineering in Xenotransplantation: What Human Transgenes Should the GTKO.hCD46 Pig Lung Donor Additionally Express?. (July 2018) - Burdorf, Lars; Redding, Emily; Laird, Christopher; Cheng, Xiangfei; Braileanu, Gheorghe; O'Neill, Natalie; Parsell, Dawn; Zhang, Tianshu; Cimeno, Arielle; Phelps, Carol J; Ayares, David L; Azimzadeh, Agnes M; et al.
Abstract : Background: Recent advances in genetic engineering have enabled generation of pigs expressing multiple transgenes as potential donors for xenotransplantation. What transgenes contribute to protect xenogeneic lungs from being injured by known xenorejection mechanisms, has not previously been systematically evaluated. Here we summarize results directly testing several individual transgenes on a platform GTKO.hCD46 in a xenogeneic lung perfusion model. Methods: GTKO.hCD46 pig lungs, additionally expressing either hEPCR, HLAE, hvWF, hTBM, hCD55 or including Neu5GC knock-out were perfused with fresh heparinized human blood for up to 8 hours. Functional parameters, as well as blood and tissue samples were analyzed and compared to lungs that did not have the respective additional genetic modification. Results: Lung "survival" was significantly increased in lungs with hEPCR and HLA-E. While HLA-E, hEPCR and hTBM expression led to reduced BTG elaboration, platelet sequestration was only markedly reduced by the expression of humanized vWF. Pulmonary vascular resistance as well as histamine elaboration showed significantly lower values in lungs with HLA-E or Neu5GcKO. The knock-out of the Neu5Gc epitope also significantly reduced thromboxane levels and activation of the coagulation cascade (F1+2). Conclusion: Several mechanisms associated with GTKO.hCD46 xenolung injury are modulated by additional expression of individual pathway-targeting human transgenes. We conclude that each of the pathways targeted by the transgenes tested, including Neu5GcKO, provide protection from non-Gal-antibody-mediated lung rejection mechanisms. We hypothesize that combinations of the beneficial genetic modifications tested here will result in further improvement of xenogeneic lung function and extension of graft survival. United Therapeutics SRA. NIH U19A1090959.